SUPPLY CHAIN MODEL OF CAPTURE FISHERIES FOR FOOD SECURITY IN THE TIME OF THE COVID-19 PANDEMIC FOR INLAND COMMUNITIES OF WEST ACEH REGENCY - Y. Zuriat; M. Rizal; M. Ghazali; Sabar Yuliana (Teunuleh Publisher, 2021)
Fish is one of the main ingredients of food security for the community. The factor of high and low levels of fish consumption is influenced by the distance to the fish landing center. West Aceh Regency, Aceh Province, has a territorial structure that stretches from the sea to the mountains. The study focuses on the level of supply (both kinds of as well as buying public power frequency) fish to the interior, by taking a sample that is the community and fish traders in sub district pantee ceremeun, West Aceh Regency. The results showed that there is no guarantee that fish will reach the hinterland every day, the supply of fish will arrive if the fish caught in the landing center of Ujong Baroh, Johan Pahlawan District, West Aceh Regency, are relatively abundant and cheap in price, with a short supply chain. Margin level reached 55%. The fish supply chain from PPI Ujong Baroh which is the largest fish landing center in West Aceh Regency to remote areas which is 60 to 70 km away, so that the quality of the fish supplied is not fresh by dozens or about 45 fish agents (muge) using motorbike vehicles and tricycle rickshaws, with the difference in supply time occurring after 13.00 until 19.00 o’clock with an average fish price of Rp. 31.600 perkilogram. Purchasing power of the community fish range 1 to 2 kilograms per household per week. In order to strengthen food security community, needs to be studied potential development and freshwater fish farming opportunities in rural areas.